Reproductive health services utilization and associated factors among university youth students in Ethiopia: A mixed-methods study - Tsiyon Birhanu Wube; Solomon Gebremichael Asgedom; Dawit Gebregziabher Abrha; Lielt Gebreselassie Gebrekirstos (Global Epidemiology)
Background: Reproductive health services utilization among youth university students is essential for their sexual and reproductive well-being. Despite growing awareness, students often face barriers—cultural, social, and economic—that limit their access to these services. Understanding service utilization patterns and associated factors is crucial for addressing unmet needs, such as limited access to family planning, maternal care, and sexual health services, as well as the lack of resources and awareness, which affect the quality of care and access to services. The study investigated the utilization of the services among youth university students, aiming to provide insights for targeted interventions and enhanced service delivery. Methods: We conducted an institutional-based cross-sectional study with 768 youth university students, using a mixed-methods approach. Participants were selected via a multistage sampling technique. Data were collected through a self-administered questionnaire, supplemented by key informant interviews and in-depth interviews. Quantitative analysis was performed using SPSS version 25, and qualitative data were transcribed and analyzed narratively through content analysis. Logistic regression was employed to identify associations with service utilization. Results: The study found that the prevalence of adequate reproductive health service utilization rate was 42.5 % (95 % CI: 38.81 % - 46.20 %), which is comparable to similar studies conducted in other low- and middle-income countries. Key factors included open discussions about reproductive health (AOR = 4.1, 95 % CI: 2.14–7.16), positive attitudes towards services (AOR = 6.03, 95 % CI: 3.72–9.75), and perceived HIV risk (AOR = 4.32, 95 % CI: 2.39–7.77). Conclusion: Utilization of reproductive health services is relatively low, with only 42.5 % reporting usage. Key factors influencing utilization include open discussions, positive attitudes towards services, and perceived HIV risk. Addressing barriers through inclusive, youth-friendly interventions such as peer education programs could significantly improve outcomes.